IMPLEMENTATION OF INNOVATIVE TECHNOLOGIES IN THE TEACHING OF SPECIAL DISCIPLINES - Khodjaev Нодир (MMIT Proceedings, 2023)
The article devoted to some aspects of implementation of innovative technologies into the educational process in teaching special disciplines in a higher educational institution.